Standard Survey Data: Insights Into Private Sector Utilization - Montagu, Dominic; Chakraborty, Nirali (Frontiers in Medicine, 2021)
Universal Health Coverage in Low- and Middle-Income Countries is increasingly expanding through incorporation of private clinics, pharmacies, and hospitals into an overall health system funded in whole or part through government-managed health insurance. This underscores the importance of policies on health provision which apply across the whole delivery system regardless of ownership status. To advance understanding of private-sector policies, and to facilitate sharing of lessons across countries with similar public-private distributions, we have analyzed data on the source of inpatient and outpatient care from 65 countries. While past studies have conducted similar analysis, ours advances the field in two ways. First, we limit our analysis to data sets from 2010 through 2019, making our study more up-to-date than past studies, while changing health seeking patterns for maternal health since 2010 means that our data set is more representative of overall inpatient care. Second, while past multi-country analysis of public-private ownership have been based on the Demographic Health Surveys, we have added to this data from the Multiple Indicator Cluster Surveys, significantly increasing the countries in our analysis. We have aggregated our analysis by WHO’s regions. Outside of the EURO region, where the private sector delivers just 4% of all healthcare services, the private sector remains significant, and in many countries represents more than half of all care. The private sector provides nearly 40% of all healthcare in PAHO, AFRO, and WPRO regions, 57% in SEARO, and 62% in EMRO. While specific countries with two recent surveys show variation in the scale of both inpatient and outpatient private provision, we did not find regional or global trends towards or away from private care within LMICs. Private inpatient care is most important for the wealthy in many countries; public vs. private care varies less, by wealth, for outpatient services.